Phytoplankton Virus Production Negatively Affected by Iron Limitation - Slagter, Hans A.; Gerringa, Loes J. A.; Brussaard, Corina P. D. (Frontiers in Marine Science, 2016)
Fe-limited monocultures of the ubiquitous algae Micromonas pusilla and Phaeocystis globosa were infected with their respective viruses (MpV and PgV) to ascertain the effect of Fe-limitation on phytoplankton host-virus dynamics. The effect of the viral shunt on Fe concentrations and bioavailability is starting to gain attention, since not only is Fe released through lysis, but also its solubility is increased by the simultaneous release of Fe-binding dissolved organic ligands. However, the effect of Fe-limitation on the process of viral lysis itself is poorly understood. In this study fine adjustment of a seawater-based culture medium including the use of ultra-clean trace metal conditions and protocols allowed for Fe-limited growth at nanomolar amounts as opposed to micromolar amounts typically employed in culturing. Viral lysates derived from Fe-limited and Fe-replete (for comparison) hosts were cross-inoculated in hosts of both Fe treatments, to judge the quality of the resulting lysate as well as the effect of Fe introduction after initial infection. For both phytoplankton host-virus systems, the virus burst size reduced strongly under Fe stress, i.e., on average 28 ± 1% of replete. Moreover, the MpV virus progeny showed highly reduced infectivity of 30 ± 7%, whereas PgV infectivity was not affected. A small addition of Fe to Fe-limited cultures coming from the Fe-replete lysate counteracted the negative effect of Fe-limitation on phytoplankton virus production to some extent (but still half of replete), implying that the physiological history of the host at the moment of infection was an important underlying factor. These results indicate that Fe-limitation has the strong potential to reduce the loss of phytoplankton due to virus infection, thereby affecting the extent of Fe-cycling through the viral shunt. To what extent this affects the contribution of viral lysis-induced organic ligand release needs further study.